Efeitos entre autoconceito e atitudes em relação à estatística e ao pensamento probabilístico e correlacional: um estudo em alunos do ensino médio no interior de São Paulo - Pineda, Kevin José Goenaga (Universidade Federal de São Carlos, 2025)
The literature shows that a significant proportion of students do not adequately understand the fundamental concepts of probability and correlation in statistics. The aim of this study was to investigate the relationship between statistical self-concept, attitudes towards statistics and probabilistic and correlational thinking schemes in secondary school students. A cross-sectional predictive design was adopted, with the participation of 760 students (370 females), assessed using the Logical Thinking Test (TOLT), the Survey of Attitudes towards Statistics (SATS) and two ad hoc questionnaires on self-concept. After an exploratory review of the variables to ensure the adequacy of the statistical analyses, the results indicated acceptable levels of attitudes and self-concept towards statistics, but unsatisfactory performance in the probabilistic and correlational aspects. Attitudes were found to have a positive influence on statistical self-concept in both sexes. However, among male students, a negative effect of attitudes towards statistics on correlational thinking was identified. These findings reinforce the importance of pedagogical strategies that address students' self-concept and attitudes in order to improve statistical teaching and learning.
Effects between self-concept and attitudes towards statistics and probabilistic and correlational thinking: a study of high school students in the interior of São Paulo state
Keywords: Autoconceito estatístico; Atitudes em relação à estatística; Pensamento probabilístico; Pensamento correlacional; Educação estatística; Statistical selfconcept; Attitudes towards statistics; Probabilistic thinking; Correlational thinking; Statistical education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM